Plural Laws but No Laws: An Overview of the Impact of Intestate Laws on Women and Children in South-East Nigeria - Eboh, Nnenna Joy; Madu, Vivian (Acta Universitatis Danubius. Juridica, 2025)
The objective of this article is to uncover the discriminatory rigors of intestate succession in South-East Nigeria. This paper finds that the legal framework of intestate succession, that is, administration of the estate of a deceased who dies without a will, is scattered. Basically, the property of a deceased who died intestate may be administered considering his or her lifestyle, marriage, or the location of the property. This means that the personal law of the intestate will come to play when determining the estate. The process of determining how the estate of an intestate should be shared is cumbersome and discriminatory especially against women. This is in addition to insufficient laws on the subject matter. Our approach is doctrinal and the lapses or lacuna uncovered will breed recommendations that will impact positively on intestacy in the South-East of Nigeria. We find that the plural legal system does not impact on the right of women and children to intestate property in the South-East of Nigeria. As a result of discriminatory inheritance practices, women and children are disadvantaged economically. They are forced to overly rely on family members for survival. This paper adds value to the call for indiscriminate succession or inheritance practices in South-East Nigeria. It further calls for the review of the laws such that women and children are given explicit rights to intestate property.